Mathematics | Study Mode

Join Discuss Share Question Share to WhatsApp
Question 1
A
6\(\frac{4}{15}\) 
B
6\(\frac{11}{15}\) 
C
7\(\frac{4}{15}\) 
D
7\(\frac{11}{15}\) 
Explanation.
Share Answer 10\(\frac{2}{5} - 6 \frac{2}{3} + 3\)

\(\frac{52}{5} - \frac{20}{3} + \frac{3}{1}\)

= \(\frac{156 - 100 + 45}{15}\)

\(\frac{156 + 45 - 100}{15}\)

= \(\frac{201 - 100}{15}\)

= \(\frac{101}{15}\)

= 6\(\frac{11}{15}\)

Correct Option:
B
Join Discuss Share Question Share to WhatsApp
Question 3
A
6cm 
B
7cm 
C
8cm 
D
9cm 
Explanation.
Share Answer volume of cube = L x L x L

512cm3 = L3

L3 = 512cm3

L = 3\(\sqrt{512}\)

L (512)\(\frac{1}{3}\)

= (29)\(\frac{1}{3}\)

23 = 8cm

Correct Option:
C
Join Discuss Share Question Share to WhatsApp
Question 4
A
\(\frac{11}{18}\) 
B
\(\frac{11}{20}\) 
C
\(\frac{7}{22}\) 
D
\(\frac{5}{19}\) 
Explanation.
Share Answer at most 2 marks = 5 + 2 + 4 students = 11 students

probability(at most 2 marks) = \(\frac{11}{20}\)

Correct Option:
B
Join Discuss Share Question Share to WhatsApp
Question 5
A
18 
B
16 
C
14 
D
12 
Explanation.
Share Answer \(\sqrt{12} ( \sqrt{48} - \sqrt{3}\))

\(\sqrt{4 \times 3} (6 \times 3 - \sqrt{3}) = 2 \sqrt{3}(4 \sqrt{3} - \sqrt{3})\)

= 2\(\sqrt{3} \times \sqrt{3} (4 - 1) 2\sqrt{9}(3) = 2 \times 3 \times 3 = 18\)

Correct Option:
A
Join Discuss Share Question Share to WhatsApp
Question 6
A
B
i and ii 
C
i and iii 
D
i, ii and iii 
Explanation.
Share Answer x > y and 3 < y; then 3 < y means that y > 3

x > 3 to give the possible

x > y > 3

Correct Option:
C
Join Discuss Share Question Share to WhatsApp
Question 7
A
B
C
D
Explanation.
Share Answer let the number be x

2\(\frac{1}{2}x + \frac{3}{4}x = 13\)

\(\frac{5}{2}x + \frac{3}{4}x = 13\)

multiply through by 4

4(\(\frac{5}{2}\))x + 4(\(\frac{3}{4}\))x = 13 x 4

2(5x) + 3x = 52

10x + 3x = 52

13x = 52

x = \(\frac{52}{13}\)

x = 4

Correct Option:
A
Join Discuss Share Question Share to WhatsApp
Question 8
A
{0, 2, 6} 
B
{1, 3} 
C
{0, 6) 
D
{9} 
Explanation.
Share Answer x = {0, 2, 4, 6}; y = {1, 2, 3, 4}; z = {1, 3}

u = {0, 1, 2, 3, 4, 5, 6}

y' = {0, 5, 6}

to find x \(\cap\) (Y' \(\cup\) Z)

first find y' \(\cup\) z = {0, 1, 3, 5, 6}

then x \(\cap\) (Y' \(\cup\) Z) = {0, 6}

Correct Option:
C
Join Discuss Share Question Share to WhatsApp
Question 9
A
{x : x = 3, x = 9} 
B
{x : x = -3, x = -9} 
C
{x : x = 3, x = -9} 
D
{x : x = -3, x = 9} 
Explanation.
Share Answer x2 = 3(2x + 9)

x2 = 6x + 27

x2 - 6x - 27 = 0

x2 - 9x + 3x - 27 = 0

x(x - 9) + 3(x - 9) = (x + 3)(x - 9) = 0

x + 3 = 0 or x - 9 = 0

x = -3 or x = 9

x = -3, x = 9

Correct Option:
D
Join Discuss Share Question Share to WhatsApp
Question 10
A
10\(sqrt{2}\) 
B
4\(sqrt{5}\) 
C
5\(sqrt{2}\) 
D
2\(sqrt{5}\) 
Explanation.
Share Answer p(4, 3) Q(2 - 1)

distance = \(\sqrt{(x_2 - x_1)^2 + (Y_2 - y_1)^2}\)

= \(\sqrt{(2 - 4)^2 + (-1 - 3)^2}\)

= \(\sqrt{(-2)^2 = (-4)^2}\)

= \(\sqrt{4 + 16}\)

= \(\sqrt{20}\)

= \(\sqrt{4 \times 5}\)

= 2\(\sqrt{5}\)

Correct Option:
D
Next Page
Question Map
Quiz link
Share Mathematics with your friends
Share to WhatsApp Share Quiz CBT mode Study mode copy link